2016
DOI: 10.1111/lcrp.12098
|View full text |Cite
|
Sign up to set email alerts
|

The effects of face‐to‐face versus live video‐feed interviewing on children's event reports

Abstract: Purpose Recent advances in technology have raised a potentially promising service to overcome difficulties associated with remote witnesses: live video‐feed interviews. The efficacy of this mode of interviewing, however, lacks empirical evidence, particularly with children in an investigative context. Methods This study explored the effects of live video‐feed compared to face‐to‐face interviewing on the memory reports of 100 children (aged 5–12). Children participated in an innocuous event and were interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…A limited amount of research has investigated computer-mediated communication for eyewitnesses. For example, typically developing children, and children with Autism Spectrum Disorder recalled more information when interviewed by an avatar than a human ( Hsu and Teoh, 2017 ), and remote interviews via Skype have been found to increase the amount of event relevant information vs. a traditional face-to-face context ( Nash et al, 2014 ; Hamilton et al, 2017 ). However, as far as we are aware this is the first empirical study of eyewitness cognition in an immersive context where both interviewee and interviewer were represented by avatars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited amount of research has investigated computer-mediated communication for eyewitnesses. For example, typically developing children, and children with Autism Spectrum Disorder recalled more information when interviewed by an avatar than a human ( Hsu and Teoh, 2017 ), and remote interviews via Skype have been found to increase the amount of event relevant information vs. a traditional face-to-face context ( Nash et al, 2014 ; Hamilton et al, 2017 ). However, as far as we are aware this is the first empirical study of eyewitness cognition in an immersive context where both interviewee and interviewer were represented by avatars.…”
Section: Discussionmentioning
confidence: 99%
“…Witnesses interviewed remotely have reported a reduction in the perceived social pressure to ‘perform,’ and have performed equally to those interviewed face-to-face, indicating that physical co-presence may not be necessary ( Nash et al, 2014 ). Similarly, children interviewed remotely using Skype Video-Mediated Communication (VMC) provided equally as informative and accurate accounts as those interviewed face-to-face ( Hamilton et al, 2017 ), and in some cases VMC reduced errors and susceptibility to leading questions ( Doherty-Sneddon and McAuley, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive load placed upon both partners in the conversational exchange in monitoring the information being asked and answered, the social distance imposed by the tele-FI approach, and the difficulties in capturing naturalistic and nonverbal social signals that may contribute to rapport, may create challenges for interviewers attempting to establish rapport across a screen (Doherty-Sneddon & McAuley, 2000;Hamilton et al, 2017), and potentially influence both child and interviewer behaviour. interview (e.g., Hamilton et al, 2017), andDickinson (2020) commented that there was no evidence that rapport was compromised during the tele-FIs. Dale and Smith (in press) speculate that tele-interviews "may be especially suited for youth who frequently use the technology and may positively respond to the personal space and feeling of control allowed by video-conferencing" (p24).…”
Section: Applying General Interviewing Considerations To Tele-fismentioning
confidence: 99%
“…We see no reason why the conclusions derived from studies of effective interviewing strategies conducted with children face-to-face would not equally apply tele-FI. As Dickinson (2020) and Hamilton et al (2017) note, the types of questions that children are posed may be more important than the means by which they are delivered. Doherty-Sneddon & McAuley (2000) found that interviewers had to engage in more "management talk" to keep younger children on camera when interviewing via video.…”
Section: Applying General Interviewing Considerations To Tele-fismentioning
confidence: 99%
“…There should be no doubt that during the COVID-19 pandemic, technology allows triers of facts to listen to witnesses, albeit imperfectly, and to resolve urgent disputes (e.g., Abruzzese 2020 ; Boisvert 2020 ; Burns 2020 ; Gerstein 2020 ; Ibrahim 2020 ; Mathieu 2020 ; McLachlin 2020 ; Reynolds 2020 ; Schmitz 2020 ). And it is evident that in some delicate situations, technology (e.g., CCTV) can facilitate the testimony of vulnerable individuals, such as rape victims and child witnesses (e.g., Bennett 2003 ; Hamilton et al 2017 ; Kenniston 2015 ). These accommodations are also recognized by the US Supreme Court and the Supreme Court of Canada (Maryland v. Craig 1990 ; R. v. J.…”
Section: The Use Of Phone and Computer Applications: A Call For Cautimentioning
confidence: 99%